Car- and ride sharing: The current state and future possibilities in Iceland - Ásta Karen Helgadóttir 1992- (2015)
The sharing economy has been gaining momentum in the world over the past decade or so. The sharing economy has been defined as the value in taking underutilized assets and making them accessible online to a community, leading to a reduced need for ownership of those assets. Iceland has only become familiar with the term in the last couple of years, and the sharing economy is slowly, but steadily gaining a foothold in Iceland, with Icelanders‘ increased use and acceptance of the sharing economy platform Airbnb for example. Sharing has always taken place in the small Icelandic community, but Icelanders have only recently started to take part in the new version of sharing: sharing with strangers and for a compensation. Because the possibilities of the sharing economy are almost endless, this research focused solely on a specific part of it: car- and ride sharing, in order to shed some light on the enormous possibilities of the economy as a whole. The question that I endeavored to answer in this thesis was: Is there a future for car- and ride sharing platforms in Iceland? In order to do that, changes in consumer mentality and various types of car- and ride sharing business models, including their positive and negative aspects, were examined. The largest car- and ride sharing businesses in the world were identified and their successes and reputations looked into. The growing interest in the sharing economy in the Icelandic society was explored, as well as the Icelandic car- and ride sharing initiatives that have been founded recently. The benefits and problems of each of the Icelandic initiatives was be determined, as well as their possibilities for improvement, and finally the future possibilities of car- and ride sharing in Iceland were be looked into. The results of this research is that Icelandic consumers and media seem to be quite positive and curious about he sharing economy. The Reykjavik City Council has also been quite open towards the possibilities of car sharing. Some people are however concerned that ...